Electrochromic Materials: Efficient Near Infrared Modulation with High Visible Transparency Using SnO2–WO3 Nanostructure for Advanced Smart Windows (Advanced Optical Materials 8/2019). Issue 8 (18th April 2019) - Nguyen, Tam Duy; Yeo, Loo Pin; Kei, Tan Chiew; Mandler, Daniel; Magdassi, Shlomo; Tok, Alfred Iing Yoong
Abstract : In article number 1801389, Tam D. Nguyen, Alfred Tok and co‐workers present the fabrication of a hybrid SnO2 –WO3 core–shell inverse opal (IO) structure by electro‐deposition of an amorphous WO3 electrochromic layer on a highly transparent SnO2 IO framework. The SnO2 –WO3 core–shell IO structure is able to block up to 90% near‐infrared radiant heat and demonstrates optimal visible transparency of about 70% in the colored state.